Optimization of Fast Moving Consumer Goods Distribution Routes Using Vehicle Routing Problem at PT Cahaya Mahakam Samarinda - Panjaitan, Irma Adelina; Wahyuda, Wahyuda; Asdi, Ridzky Zul (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
PT Cahaya Mahakam Samarinda, as one of the companies engaged in the distribution of fast-moving consumer goods, serves a variety of customers, including wholesalers, small shops, and food businesses. Based on the initial observations that have been made, the determination of distribution routes is carried out by the warehouse manager, who subjectively determines the route based on personal observations before the driver delivers consumer products because the company does not yet have the appropriate tools or methods to determine the route. This sometimes forces drivers to search for customer locations directly in the field if they have never delivered to that customer before, and sometimes there are inaccuracies in selecting the delivery route to the next customer. In this problem, it falls under the Vehicle Routing Problem, which is solved using the cluster first, route second approach with the Sweep method to create clusters and Nearest Neighbor with manual calculations, as well as Branch and Bound with calculations using the WinQSB software to determine the route for each created cluster. The results of both route creation methods were compared with the initial route. Based on the research results, the Sweep method produced 9 fewer clusters compared to the initial route of 11 clusters. In route determination, the Nearest Neighbor method resulted in a distance savings of 55.4 km (20.11%) and a cost savings of IDR 74,190.43. The Branch and Bound method resulted in savings of 64.6 km (23.47%) and cost savings of IDR 93,144.07.